Self‐evaluation of duration of adjuvant chemotherapy side effects in breast cancer patients: A prospective study - Danilo Galizia; Andrea Milani; Elena Geuna; Rossella Martinello; Celeste Cagnazzo; Manuela Foresto; Virginia Longo; Paola Berchialla; Gianfranca Solinas; Adele Calori; Bruna Grasso; Chiara Volpone; et al. (Cancer Medicine)
Abstract Background We recently reported that self‐evaluation of the incidence and severity of treatment‐related side effects (TSEs) using a National Cancer Institute (NCI) Common Terminology Criteria for Adverse Events (CTCAE) v4.0‐based questionnaire was feasible and more informative than doctor reports in patients undergoing standard adjuvant chemotherapy for operable breast cancer. Here, we compare self‐ and doctor‐evaluated day of onset and duration of TSEs in the same population. Patients and methods Six hundred and four patients were enrolled at 11 sites in Italy. CTCAE v4.0 definitions of grade of severity of nausea, vomiting, constipation, anorexia, dysgeusia, diarrhea, fatigue, pain, paresthesia, and dyspnea were translated into Italian and rephrased. Questionnaires were administered after the first and third chemotherapy cycles. At each time‐point, information on TSEs was extracted from the medical charts and compared to patient questionnaires. Results A total of 594 and 573 paired patient and doctor questionnaires were collected after cycles one and three, respectively. TSE duration was significantly longer when reported by patients compared to doctors for six and seven of ten items after cycles one and three, respectively. Due to the combined effect of doctor underreporting of TSE incidence and duration, the mean percentages of cycle days with TSEs were significantly higher for all ten items when based on patient reports. Day of onset could not be evaluated because of insufficient numbers of complete records. Conclusions Self‐reporting TSE duration is feasible using a CTCAE‐derived questionnaire. As doctors tend to underestimate TSE incidence and duration, patient‐reported outcomes should be incorporated into clinical practice, perhaps using eHealth technologies, to harness their potential to better estimate total TSE burden.